Subharmonic Almost Periodic Functions of Slow Growth - Favorov, S. Yu.; Rakhnin, A. V. (Журнал математичної фізики, аналізу, геометрії, 2007)
We obtain a complete description of the Riesz measures of almost periodic subharmonic functions with at most of linear growth on ℂ . As a consequence we get a complete description of zero sets for the class of entire functions of exponential type with almost periodic modula. Mathematics Subject Classification: 31A05, 42A75, 30D15.